2016
DOI: 10.1002/ajmg.b.32424
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mRNA analysis of behavioral and genetic mouse models of aggression

Abstract: Mouse models of aggression have traditionally compared strains, most notably BALB/cJ and C57BL/6. However, these strains were not designed to study aggression despite differences in aggression-related traits and distinct reactivity to stress. This study evaluated expression of genes differentially regulated in a stress (behavioral) mouse model of aggression with those from a recent genetic mouse model aggression. The study used a discovery-replication design using two independent mRNA studies from mouse brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Nevertheless, similar pathways such as synaptic development, axon guidance and MAPK signaling emerge when examining genes from the top GWAS findings (P ≤ 5e-05, 11 ). These pathways were also enriched in genes identified through transcriptomic studies of animal models of aggression in mice 27 , 28 , rats 29 , zebrafish 30 and Drosophila 31 . With increasing sample sizes, some of these genes and, perhaps, additional risk loci may emerge in future GWASs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, similar pathways such as synaptic development, axon guidance and MAPK signaling emerge when examining genes from the top GWAS findings (P ≤ 5e-05, 11 ). These pathways were also enriched in genes identified through transcriptomic studies of animal models of aggression in mice 27 , 28 , rats 29 , zebrafish 30 and Drosophila 31 . With increasing sample sizes, some of these genes and, perhaps, additional risk loci may emerge in future GWASs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, both 5‐HT1B ‐ [Saudou et al, ] and MAOA ‐ [Cases et al, ] knockout mice have been shown to display increased aggressive behavior compared to control mice. Transcriptomic characterisation of three pairs of mouse lines selectively bred for aggression found that the NF‐kB and MAPK gene pathways (redox‐signaling pathways) in the prefrontal cortex (PFC) are implicated in aggressive behavior and identified several novel candidate genes [Malki et al, , ; Freudenberg et al, ; Veroude et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the present study has revealed generalized increases of oxidative stress markers in the brain to parallel elevated scores of aggressive behaviour in mouse model emotional stress and these changes were reversed by the administration of thiamine and benfotiamine. Treatment with benfotiamine had a greater effect on reversing brain oxidative stress than thiamine, supporting previous observations that there may be increased bioavailability for benfotiaine in comparison to thiamine (Pan et al, 2010; (Rammal et al, 2010;Cline et al, 2015a;Malki et al, 2016).…”
Section: Discussionsupporting
confidence: 77%
“…Both genetic and environmental factors have been shown to regulate aggressive traits via complex codependent mechanisms (Caspi et al 2002;, but a causal role for environmental stress is well documented (Angkaw et al, 2013;Fanning et al, 2015Fanning et al, , 2017 and is associated with overt aggression in humans (Kim and Haller, 2007;Kessler et al, 2015). Experimental models have also provided support for this relationship (Veenema and Neumann, 2007;Rammal et al, 2010;Malki et al, 2016). In particular, emotional stress, which is referred to as state that is primarily triggered by the perception and cognitive evaluation of adverse events rather than a disturbance of physical nature (Chrouses and Gold, 1992;, appears to be the type of stress that most frequently results in overt aggressiveness (Angkaw et al, 2013;Fanning et al, 2015Fanning et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%